2017
DOI: 10.2174/1874312901711010043
|View full text |Cite
|
Sign up to set email alerts
|

The Use of patient Reported Outcome Measures for Rheumatoid Arthritis in Japan: A Systematic Literature Review

Abstract: Background:Patient-reported outcomes (PRO) obtained through routine medical care may identify patients’ day-to-day burden and help tackle the disease from the patients’ perspective. However, there is a paucity of information regarding the availability of PRO data and PRO tools for rheumatoid arthritis (RA) in Japan.Objective: We reviewed the literature on PRO data availability and to identify PRO measures implemented in Japan for RA patients. Method: We conducted a systematic literature review using ICHUSHI an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…According to the studies, stakeholders were generally positive about the implementation of PRMs in maternity care, recognized the potential benefits and supported the systematic integration of PRMs into routine clinical practice. This main finding was consistent with other reviews that studied the acceptability of using and implementing PRMs in other clinical contexts outside maternity care 19,45,46 …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…According to the studies, stakeholders were generally positive about the implementation of PRMs in maternity care, recognized the potential benefits and supported the systematic integration of PRMs into routine clinical practice. This main finding was consistent with other reviews that studied the acceptability of using and implementing PRMs in other clinical contexts outside maternity care 19,45,46 …”
Section: Discussionsupporting
confidence: 91%
“…This main finding was consistent with other reviews that studied the acceptability of using and implementing PRMs in other clinical contexts outside maternity care. 19,45,46 According to included studies, women's acceptance of PRMs as an integrated part of maternity care could vary with timing, modes, and platforms of PRMs administration. While some studies reported that women expressed their preference for and satisfaction with digital responses to PRMs questions, 21,24,27,29,32 synthesized data from other studies suggested that women were more likely to respond to paper-based questionnaires than web-or app-based ones.…”
Section: Discussionmentioning
confidence: 99%
“…Rheumatoid arthritis (RA) is a chronic, progressive, systemic inflammatory autoimmune disease that causes joint deformity, pain, and functional disability [1,2]. RA affects approximately 0.5-1% of the population globally [3].…”
Section: Introductionmentioning
confidence: 99%
“…To date, however, there have been no reports on residual symptoms as indicated by PROs among patients achieving remission or LDA after previous inadequate responses to MTX, or in Japanese patients achieving remission or LDA. Further, there are relatively limited data available in general about PROs in Japanese patients with RA [21]. Having a better understanding of residual symptoms and how disease activity relates to PROs in these patients, including those from different populations with different cultural norms that could affect responses, may help facilitate better treatment strategies.…”
Section: Introductionmentioning
confidence: 99%